(untitled) (Confluenţe Bibliologice, 2026)
This article examines the 1473 Humor Tetraevangelium, copied by Hieromonk Nicodim under Ștefan the Great’s orders. Highlighted are its exquisite miniatures, the authentic votive portrait of the voivode, and rich gold ornamentation, tracing the manuscript’s journey through centuries and its pivotal role in the development of medieval Romanian miniature art.